The main problems of building the system of statistical indicators in the field of cryonics - M. V. Karmanov; S. I. Kuzin; E. S. Pozhidaeva (Вестник университета)
Cryonics as rather inconsistent, but constantly developing sphere of activity of modern society cannot be adequately estimated by means of separate private indicators or even their enlarged groups. This requires the development of a system of indicators that includes not only the traditional parameters of material and technical base and human capacity, but also the scale, intensity, results and consequences of cryonic activities. The key problems of the system of indicators of critical activity statistics, its features and possible approaches to its construction have been considered in the article.